Laying the groundwork: Exploring pesticide exposure and genetic factors in south-eastern Brazilian farmers - Débora Dummer Meira; Victor Nogueira Da Gama Kohls; Matheus Correia Casotti; Luana Santos Louro; Gabriel Mendonça Santana; Thomas Erik Santos Louro; Adriana Madeira Alvares da Silva; Lorena Souza Castro Altoé; Raquel Reis Trabach; Sonia Groisman; Elizeu Fagundes de Carvalho; Jamila Alessandra Perini Machado; et al. (Current Research in Toxicology)
Brazil is the world leader in pesticide consumption, and its indiscriminate use puts farmers’ health at risk. The CYP2C9 gene encodes the CYP2C9 enzyme, which metabolizes several endogenous substrates and specific xenobiotics, especially pesticides. Our goal is to study the risk of pesticide use, especially the herbicide glyphosate, in the development of diseases and the association with two CYP2C9 polymorphisms, in farmers living in the southern region of Espírito Santo state, Brazil. The allelic frequency of CYP2C9*1, CYP2C9*2 and CYP2C9*3 was determined in blood samples from individuals exposed or not to pesticides using real-time PCR. 304 blood samples were analyzed, dividing CYP2C9 genotypes into three metabolization classes: normal, intermediate, and slow. Our results indicate that normal metabolizers may be more susceptible to conditions such as high blood pressure, cardiovascular disease, and kidney problems. Intermediate metabolizers show an association with attention deficit disorder and miscarriages, suggesting that farmers’ symptoms correlated with their CYP2C9 genotype. Insufficient data prevented conclusions about slow metabolizers (*2 and/or *3). These findings suggest that the CYP2C9 genotype may influence the way farmers exposed to pesticides respond, but more research is needed to clarify causality and investigate other possible health effects. As an introductory effort, this study provides insights into the complex relationship between genetic variations and pesticide exposure, laying the groundwork for future research. This pioneering work on associations between specific genetic variations and health risks with pesticide exposure, emphasizes the importance of personalized medicine and stricter regulation of pesticide use for public health and occupational safety.